Peranan Pemerintah Daerah, Sumber Daya Manusia, Lingkungan Wirausaha Terhadap Pemberdayaan UMKM dan Penyerapan Tenaga Kerja Di Kabupaten Gowa - Karno B; Andi Widiawati (STIM-LPI Makassar, 2021)
This study aims to describe the role of local government, human resources, entrepreneurial environment in empowering UMKM and absorbing labor in Gowa Regency. One of the reasons for conducting this research is that UMKM in Gowa Regency experienced an increasing trend from 6,937 units in 2017 to 7,104 units in 2018, and increased to 7,233 in 2019. Therefore, researchers feel it is important to see how the role of Local Government, Human Resources and the Entrepreneurial Environment in Empowering UMKM and absorbing labor in Gowa Regency. The method used in this study is a descriptive qualitative method, namely parsing explanations and analyzing secondary data. The results of this study indicate that Micro, Small and Medium Enterprises are businesses that play an important role in the community's economy, because they can encourage the rate of economic growth and employment in Gowa Regency. The role of UMKM for the welfare of society can be seen from: Their position as a major player in economic activity in various sectors, the largest provider of employment opportunities, an important player in local business development and community empowerment. However, on the other hand the Regional Government in creating a conducive climate for the growth and development of UMKM has not been fully realized, especially in terms of marketing of UMKM products.